EFEKTIVITAS LATIHAN LARI ZIG-ZAG DENGAN SHUTTLE RUN TERHADAP KELINCAHAN PADA PEMAIN SEPAKBOLA DI SMAN KEBERBAKATAN OLAHRAGA MAKASSAR - Darwis Durahim; Ardiansah Ardiansah; Siti Nurul Fajriah; Andi Halimah (Media Fisioterapi Politeknik Kesehatan Makassar, 2021)
Background : Agility is defined as a fast movement of the whole body with a change of speed or direction in response to a stimulus. It is an important motor skill in sports that involve multi-directional changes.Methods: This research is an experimental study using a quasi-experimental design using the pre test-post test two group design method. This study aims to determine the differences in the effectiveness of zig-zag running training with shuttle run training on agility in soccer players. The number of samples was 24 people using total sampling which were divided randomly into 2 groups, namely treatment group 1 which was given zig-zag running training, as many as 12 people and treatment group 2 which was given shuttle run training as many as 12 people using the Illinois agility run test measurement .Results: Based on the analysis of the Wilcoxon Test, it shows that zig-zag running practice can produce significant agility changes with an average increase of 1.14 seconds and p value = 0.002 (p <0.05), while shuttle run training also produces changes in agility which is significant with an average increase of 0.50 seconds and a value of p = 0.002 (p <0.05). Based on the analysis of the Mann-Whitney test, it was found that there was a significant difference in effectiveness between the zig-zag running exercise and the shuttle run with a value of p = 0.001 (p <0.05), seen from the mean value indicating that the zig-zag running exercise was more effective than the shuttle run practice.Conclusion: The zig-zag running exercise is more effective than the shuttle run exercise on the agility of football players at the Makassar Kebatakan Sports High School.Keywords : Zig-Zag run, Shuttle run, illinois agility run test, agility